Perencanaan Fleet Menggunakan Metode Monte Carlo dengan Pendekatan Cycle Time di PT. ANTAM Tbk, UBP Bauksit Tayan, Kalimantan Barat - Resi Hutriayu; Adree Octova (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. PT. ANTAM Tbk. UBPB Tayan, West Kalimantan conducts exploration and exploitation of metal minerals in the Tayan Hilir, West Kalimantan. PT. ANTAM Tbk. UBPB Tayan is a bauxite mining which is one of the operational activities originating from the washing crude bauxite (CBx) from mining activities to produce wash bauxite (WBx) by doing two activities in the process of transporting material to washing plant area. PT. ANTAM Tbk. UBPB Tayan undertake mining activities at front of Bukit 7B with a production target of 3.175.000 wmt in the production target WBx the planned CBx mining production is 6,487,242 wmt in 2019. Based on field observations, the production target in Bukit 7B area PT. ANTAM Tbk. UBPB Tayan has still not been reached, and the actual fleet used today is inadequate to achieve the next month's production target. Efforts to produce not achieving production targets by planning using the Monte carlo method with a time cycle approach. Related to production targets and the number of tools that will be used by the company in fleet planning, work composition, effectiveness, and compatibility of the tools in the two work plans are able to minimize the achievement of production targets. Where the probability value of 50% and 100%.Keywords: Crude Bauxite, Production, Fleet, Cycle Time anda The Monte Carlo Method